2022
DOI: 10.1186/s12915-022-01411-2
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenesis of the odorant receptor co-receptor (Orco) reveals severe olfactory defects in the crop pest moth Helicoverpa armigera

Abstract: Background Odorant receptors (ORs) as odorant-gated ion channels play a crucial role in insect olfaction. They are formed by a heteromultimeric complex of the odorant receptor co-receptor (Orco) and a ligand-selective Or. Other types of olfactory receptor proteins, such as ionotropic receptors (IRs) and some gustatory receptors (GRs), are also involved in the olfactory system of insects. Orco as an obligatory subunit of ORs is highly conserved, providing an opportunity to systematically evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 93 publications
0
11
0
Order By: Relevance
“…One is as Zhang et al (2019) discovered that both Orco pathway and IRs pathway are involved in acid sensing. Alternatively, as in Helicoverpa armigera, defects in Orco pathway do not alter the insect's response to acid (Fan et al, 2022). An interesting question for future research is whether Orco pathway is involved in acid sensing in A. hygrophila along with IRs pathway.…”
Section: Discussionmentioning
confidence: 98%
“…One is as Zhang et al (2019) discovered that both Orco pathway and IRs pathway are involved in acid sensing. Alternatively, as in Helicoverpa armigera, defects in Orco pathway do not alter the insect's response to acid (Fan et al, 2022). An interesting question for future research is whether Orco pathway is involved in acid sensing in A. hygrophila along with IRs pathway.…”
Section: Discussionmentioning
confidence: 98%
“…The PER percentage of Gr6 −/− adults was not disappeared when the antennae and tarsi were stimulated by high fructose concentrations (Figure 7F and 7I ); this indicates that fructosetuned GRs other than Gr6 were involved. Previous studies have shown that Gr9 (Gr4 in Jiang et al, 2015 ), as an ortholog of DmelGr43a and BmorGr9, is a fructose-tuned GR (Ai et showed that Orco knockout had no significant effect on the expression of most OR, IR and GR genes in adult antennae of H. armigera although some genes were up-or down-regulated to a certain extent (Fan et al 2022 ). To elucidate the precise molecular mechanisms of sugar reception in H. armigera is necessary to compare a series of single, double and even multiple Gr knock-out lines and investigate the downstream effects of the GRs.…”
Section: Discussionmentioning
confidence: 99%
“…, 2019; Fan et al. , 2022). Chemoreceptors expressed in larvae are generally related to food sources.…”
Section: Introductionmentioning
confidence: 99%
“…It has the highest expression among all ORs in most cases and determines the olfactory sensitivity of insects. Insects lose most olfaction when Orco is knocked down or knocked out (Fandino et al, 2019;Fan et al, 2022). Chemoreceptors expressed in larvae are generally related to food sources.…”
Section: Introductionmentioning
confidence: 99%